Structural changes of the corpus callosum in tinnitus - Diesch, Eugen; Schummer, Verena; Kramer, Martin; Rupp, André (Frontiers in systems neuroscience, 2012)
Objectives: In tinnitus, several brain regions seem to be structurally altered, including the medial partition of Heschl's gyrus (mHG), the site of the primary auditory cortex. The mHG is smaller in tinnitus patients than in healthy controls. The corpus callosum (CC) is the main interhemispheric commissure of the brain connecting the auditory areas of the left and the right hemisphere. Here, we investigate whether tinnitus status is associated with CC volume. Methods: The midsagittal cross-sectional area of the CC was examined in tinnitus patients and healthy controls in which an examination of the mHG had been carried out earlier. The CC was extracted and segmented into subregions which were defined according to the most common CC morphometry schemes introduced by Witelson (1989) and Hofer and Frahm (2006). Results: For both CC segmentation schemes, the CC posterior midbody was smaller in male patients than in male healthy controls and the isthmus, the anterior midbody, and the genou were larger in female patients than in female controls. With CC size normalized relative to mHG volume, the normalized CC splenium was larger in male patients than male controls and the normalized CC splenium, the isthmus and the genou were larger in female patients than female controls. Normalized CC segment size expresses callosal interconnectivity relative to auditory cortex volume. Conclusion: It may be argued that the predominant function of the corpus callosum is excitatory. The stronger callosal interconnectivity in tinnitus patients, compared to healthy controls, may facilitate the emergence and maintenance of a positive feedback loop between tinnitus generators located in the two hemispheres.